1987
DOI: 10.1007/bf02396613
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel pseudo-obstruction in Kawasaki disease

Abstract: Between June 1977 and May 1986, 310 patients with Kawasaki disease were admitted to Shizuoka Children's Hospital. Among these patients, seven showed the symptoms of intestinal paralysis during the acute stage. We present three of these cases who showed typical intestinal pseudo-obstruction radiologically, and discuss the treatment of this type of intestinal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
37
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…12,13,18,19 Intestinal pseudoobstruction has been reported to occur in up to 2% to 3% of children with KD. 20,21 A clue to the development of this complication, as demonstrated in the present case, is the presence of persistent vomiting during the course of the illness, which is uncommon in KD. In contrast to those who develop mechanical bowel obstruction secondary to ischemic strictures, in which vomiting generally appears 2 to 4 weeks after the acute illness, [13][14][15][16] vomiting in pseudoobstruction tends to be seen early.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…12,13,18,19 Intestinal pseudoobstruction has been reported to occur in up to 2% to 3% of children with KD. 20,21 A clue to the development of this complication, as demonstrated in the present case, is the presence of persistent vomiting during the course of the illness, which is uncommon in KD. In contrast to those who develop mechanical bowel obstruction secondary to ischemic strictures, in which vomiting generally appears 2 to 4 weeks after the acute illness, [13][14][15][16] vomiting in pseudoobstruction tends to be seen early.…”
Section: Discussionsupporting
confidence: 50%
“…In the report by Miyake et al, 20 7 of 310 patients with KD developed pseudoobstruction, of whom 5 were found to have coronary artery disease. Similarly Zulian et al 1 found a coronary artery aneurysm rate of 50% in their report of 10 children with KD presenting with a surgical abdomen, of whom 3 were felt to have intestinal pseudoobstruction.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations